Reconstruction of Islamic Religious Education Based On The Values of Rahmatan Lil ‘Alamin - Arief Surya Zulkifli; Iskandar Mirza; Iyad Suryadi (International Journal of Science and Environment (IJSE), 2026)
Islamic Religious Education plays a strategic role in shaping students’ character to become religious, humanistic, tolerant, and moderate individuals. This study aims to analyze the concept of reconstructing Islamic Religious Education based on the values of rahmatan lil ‘alamin as a paradigm of humanistic and moderate Islamic education. The study employs a qualitative approach using the library research method. The findings reveal that the reconstruction of Islamic Religious Education grounded in the values of rahmatan lil ‘alamin constitutes a strategic step toward developing a humanistic, moderate, and inclusive Islamic educational system. Values such as compassion, tolerance, moderation, and justice should serve as the primary foundation in curriculum development, learning methods, character education, and the strengthening of teachers’ competencies. The implementation of rahmatan lil ‘alamin values in Islamic Religious Education can provide a solution for addressing the challenges of globalization, radicalism, and the moral crisis among younger generations.